Diamond as a Platform for Integrated Quantum Photonics. Issue 3 (11th October 2018) - Lenzini, Francesco; Gruhler, Nico; Walter, Nicolai; Pernice, Wolfram H. P.
Abstract: Integrated quantum photonics enables the generation, manipulation, and detection of quantum states of light in miniaturized waveguide circuits. Implementation of these three operations in a single integrated platform is a crucial step toward a fully scalable approach to quantum photonic technologies. In this context, diamond has emerged as a particularly promising material as it naturally combines a large transparency range for the fabrication of low‐loss photonic circuits, and a variety of optically active defects for the realization of efficient single‐photon emitters. Furthermore, its high Young's modulus makes it ideal for the implementation of tunable optomechanical devices for active quantum state manipulation. This review reports recent progress on the realization of the main components required for a diamond‐based integrated quantum photonic architecture: single‐photon emitters, static and actively tunable waveguide circuits, and, as a last building block, integrated superconducting single‐photon detectors. Abstract : A central goal of quantum photonic technologies is the integration of single‐photon sources, detectors, and optical circuits on a common material platform. This review reports recent progress toward the realization of a diamond‐based integrated quantum photonic architecture, including single‐photon emitters based on diamond defects, static and tunable optomechanical waveguide circuits, and, as a last building block, integrated superconducting single‐photon detectors.